2020
DOI: 10.1007/s12311-020-01191-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Midline Cerebellar rTMS on Human Pharyngeal Cortical Activity in the Intact Swallowing Motor System

Abstract: We sought to compare the effects of 10 Hz cerebellar vermis (vs. unilateral hemispheric and sham) repetitive transcranial magnetic stimulation (rTMS) on cortical neuroelectrical activity and thereafter 10 Hz cerebellar vermis (vs. sham) rTMS on swallowing behaviour. Healthy participants (n = 25) were randomly allocated to receive vermis, unilateral hemisphere or sham 10 Hz cerebellar rTMS. Recordings were made using pharyngeal electromyography and manometry catheters, obtaining motor-evoked potentials (MEPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Additionally, a study demonstrated that cTBS stimulating cerebellar vermis could lead to a significant influence on balance function as body sway increases ( Colnaghi et al, 2017 ). For other effects on humans, Sasegbon et al (2021) found that TMS on cerebellar vermis has an inhibitory effect on pharyngeal cortical activity and swallowing. Moreover, Argyropoulos et al (2011) demonstrated that TBS of the right neocerebellar vermis can selectively disrupt the practice-induced acceleration of lexical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study demonstrated that cTBS stimulating cerebellar vermis could lead to a significant influence on balance function as body sway increases ( Colnaghi et al, 2017 ). For other effects on humans, Sasegbon et al (2021) found that TMS on cerebellar vermis has an inhibitory effect on pharyngeal cortical activity and swallowing. Moreover, Argyropoulos et al (2011) demonstrated that TBS of the right neocerebellar vermis can selectively disrupt the practice-induced acceleration of lexical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effects of cerebellar neurostimulation appear to be site-specific. Studies have found that rTMS or tDCS applied over the midline of cerebellum result in suppressive effects on pharyngeal cortical excitability and swallowing behavior or skill learning [80,81]. While cerebellar neurostimulation may appear to have therapeutic potential for dysphagia, most of the data come from healthy volunteer studies.…”
Section: Central (Cortical and Cerebellar) Neurostimulationmentioning
confidence: 99%
“…Pharyngeal recordings were made using a trans-nasally inserted intraluminal catheter (Gaeltec, Isle of Skye, UK) as described before 31 . APB EMG signals for recording APB MEPs were used as a control and acquired as previously reported 32 .…”
Section: Study Proceduresmentioning
confidence: 99%
“…Following this, single-pulse TMS was used to locate pharyngeal motor cortical hotspots bilaterally and the APB motor cortical hotspot on the hemisphere with the lowest pharyngeal RMT. RMTs over pharyngeal and APB areas were determined as has been described in previous studies 32 .…”
Section: Videofluoroscopy (Vfs)mentioning
confidence: 99%